Virtual Inertia Control Strategy in Microgrid Based on Virtual Synchronous Generator Technology - Shi, Kai; Ye, Haihan; Song, Wentao; Zhou, Guanglei (IEEE access, 2018)
Although the virtual inertia algorithm can be used to enhance the inertia of microgrid system, the strong coupling and low precision always limit its popularization and application. Therefore, a novel virtual inertia control strategy is proposed in this paper. Combining with the potential inertia advantages of virtual synchronous generator (VSG) technology, the poor compatibility between the virtual inertia principle and the energy storage control algorithm is analyzed in detail. In order to improve the control precision, this paper focuses on the analysis of frequency response characteristics of alternating current (ac) side and then regulates the ac frequency more directly and accurately by the virtual inertia generated from the energy storage device and the grid-connected inverter. Thus, additional droop characteristic, particular control algorithm of energy storage device, and power given module are designed, respectively, to make the system provide virtual inertia power support actively under multi disturbance operation. The novel virtual inertia control strategy can effectively deal with all kinds of wind speed and ac load mutation and restrain the frequency variation on ac side. Finally, the correctness and feasibility of the proposed scheme are verified by the simulation results.